The Effect of Scaffold Modulus on the Morphology and Remodeling of Fetal Mesenchymal Stem Cells - Rufaihah, Abdul Jalil; Cheyyatraivendran, Suganya; Mazlan, Muhammad Danial Mohd; Lim, Kenrich; Chong, Mark Seow Khoon; Mattar, Citra Nurfarah Zaini; Chan, Jerry Kok Yen; Kofidis, Theodoros; Seliktar, Dror (Frontiers in Physiology, 2018)
Hydrogel materials have been successfully used as matrices to explore the role of biophysical and biochemical stimuli in directing stem cell behavior. Here, we present our findings on the role of modulus in guiding bone marrow fetal mesenchymal stem cell (BMfMSC) fate determination using semi-synthetic hydrogels made from PEG-fibrinogen (PF). The BMfMSCs were cultivated in the PF for up to 2 weeks to study the influence of matrix modulus (i.e., cross-linking density of the PF) on BMfMSC survival, morphology and integrin expression. Both two-dimensional (2D) and three-dimensional (3D) culture conditions were employed to examine the BMfMSCs as single cells or as cell spheroids. The hydrogel modulus affected the rate of BMfMSC metabolic activity, the integrin expression levels and the cell morphology, both as single cells and as spheroids. The cell seeding density was also found to be an important parameter of the system in that high densities were favorable in facilitating more cell-to-cell contacts that favored higher metabolic activity. Our findings provide important insight about design of a hydrogel scaffold that can be used to optimize the biological response of BMfMSCs for various tissue engineering applications.